Pengembangan UMKM Melalui Strategi Pemasaran Dan Penguatan Legalitas Usaha (NIB, PIRT, Halal) - Fatimah, Feti; Rusdiyanto; Rahayu, Jekti; Sumowo, Seno (Universitas Muhammadiyah Jember, 2025)
Wuluhan is a sub-district located in the south of Jember Regency. The location of Wuluhan District is close to Ambulu, Puger and Balung Districts. The government center is in Dukuh Dempok Village. There are seven villages in Wuluhan District, namely: Lojejer, Ampel, Dukuh Dempok, Taman Sari, Glundengan, Tanjungrejo and Kesilir. MSMEs in Kesilir Village are starting to try to get back on their feet after being affected by the Covid pandemic. The development that must be carried out by MSMEs is through marketing strategies and strengthening business legality (NIB, PIRT, Halal). Activities agreed upon between the implementation team and partners include: First, emphasizing training and assistance in determining and determining marketing strategies, and the second priority scale is emphasizing training and assistance regarding strengthening business legality (NIB, PIRT, Halal).